Biomaterials science and tissue engineering : principles and methods - Basu, Bikramjit (UK Cambridge University Press, 2017)
"Provides an encyclopedic coverage of biomaterials science which, at the same time, has enough to interest the biomedical scientists and engineers"--
Materials for biomedical applications -- Tissue engineering scaffolds : principles and properties -- Conventional and advanced manufacturing of biomaterials -- Probing structure of materials at multiple length scales -- Mechanical properties : principles and assessment -- Cells, proteins and nucleic acids : structure and properties -- Cell-material interaction and biocompatibility -- Probing cell response, in vitro -- Bacterial growth and biofilm formation -- Probing tissue response, in vivo -- Case study : corrosion and wear of selected Ti-alloys -- Case study : calcium phosphate-mullite composites -- Case study : compression moulded HDPE-based hybrid biocomposites -- Case study : phase stability, bactericidal and cytocompatibility of HA-Ag -- Case study : HA-CaTiO3 based multifunctional composites -- Case study : compatibility of neuronal/cardiac cells with patterned substrates -- Perspectives.
Includes bibliographical references and index.
Keywords: Biocompatible Materials; Tissue Engineering; Molecular Probe Techniques